PENINGKATAN MINAT BELAJAR PENDIDIKAN JASMANNI MELALUI PENDEKATAN TAKTIS - Budiman, Budiman (Jurnal Olahraga, 2017)
The purpose of this study was to determine and test the effect of the tactical approach model on students' interest in physical education learning. The method used is an experimental method with a Randomized Control Group Pretest-Posttest Design. The population in this study was 249th grade students of SMP Negeri 3 Bayongbong, totaling 249 people. The sample chosen was 60 people taken by simple random sampling. Based on this technique, 30 experimental group samples and 30 control group samples were obtained. The instrument used to measure Physical Education interest is using a student interest scale test. Statistical calculations in testing hypotheses using SPSS 23 through paired t-test Paired sample t test. The results of data analysis showed that the tactical approach had an influence on students' interests with the Sig. 2-tailed 0.004 <0.05. Based on the results of data processing and analysis, it can be concluded that the tactical approach model has a significant influence on student interest